Alienation In Mula Khalil Mushakhti - Ahmed, Dawlat M. (Humanities Journal of University of Zakho, 2016)
This study is addresses the aspect of alienation in Mula Khalil Mushakhti, where it is taken as a sample to the poets of his era. This is because, basically, the poets from the northern Kurdistan all participated side by side in the activity at that phase. The bad conditions were the major reason for the appearance of the aspect of alienation at that time.The importance of this research paper lies in the fact that it is a practical research which examines the aspect of alienation in all its trends on one hand. On the other hand, this study is regarded as a big contribution in the field of literary research and generally for any researcher who would like to conduct researches in this field with regards to alienation and specifically alienation in the Kurdish literature. This is specifically to serve and develop the pure literature of alienation in the literary research.